Incremental clinical value of intraplaque neovascularization in predicting recurrent ischemic stroke - Liuping Cui; Ran Liu; Fubo Zhou; Bing Tian; Ying Chen; Yingqi Xing (Annals of Clinical and Translational Neurology)
Abstract Objective Carotid intraplaque neovascularization (IPN) detected by contrast‐enhanced ultrasound (CEUS) is a risk factor for recurrent ischemic stroke. However, it is still unclear whether IPN can be used to accurately identify patients with recurrent ischemic stroke in clinical practice. Herein, we investigated the clinical predictive value of IPN for recurrent ischemic stroke in a real‐world setting. Methods We enrolled 200 patients with ischemic stroke and atherosclerotic carotid stenosis who were followed up for 2 years. The endpoint was recurrent ischemic stroke. Cox regression and subgroup analyses were employed to assess whether treatment affected the relationship between IPN and recurrent ischemic stroke. The net classification index (NRI) and integrated discriminant improvement index (IDI) were used to validate the additional clinical value of IPN in identifying recurrent ischemic stroke. Results During the 2‐year follow‐up, 36 patients experienced recurrent ischemic stroke. Cox regression analyses showed that IPN (grade 2), hypoechoic plaque, high homocysteine levels, and smoking were independent risk factors for recurrent ischemic stroke. Additional IPN evaluation may increase the NRI (0.512; 95% confidence interval [CI]: 0.083–0.624) and IDI (0.151; 95% CI: 0.010–0.213) for identifying high‐risk patients with recurrent ischemic stroke. In addition, in the subgroup undergoing revascularization, the proportion of IPN (grade 2) was significantly higher in patients with recurrent ischemic stroke than in patients with nonrecurrent ischemic stroke (p = 0.001). Interpretation In clinical settings, IPN, assessed by CEUS, may provide additional clinical value for predicting recurrent ischemic stroke, helping to identify patients with ischemic stroke who require close follow‐up.